Pengembangan Potensi Budaya Ekowisata melalui Pemberdayaan Masyarakat Desa Wisata Candirejo Borobudur Jawa Tengah - Syaiful Ade Septemuryantoro (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2020)
The research that will be proposed has the objective of identifying the development of ecotourism in the Candirejo village. The development of ecotourism in the Village of Candirejo has the goal of making a positive impact in the environment of Candirejo. The positive impact expected by the community and identification of ecotourism development is expected to be a source of income of the Candirejo village. This research uses a descriptive-analytical technique, qualitative approach method is a way to get data and collecting data through Candirejo villagers. Interview techniques and document collection are ways to get data to this research. The technique used to take samples in the study is using the purposive sampling technique, then the data to be collected in the form of observation to the community, interviews and document review. Community empowerment in the village of Candirejo has been going well. Candirejo Village cooperates with related agencies. the collaboration was carried out to develop the potential of the village